PEMBAJAKAN KARYA JURNALISTIK DI MEDIA INTERNET PIRACY OF LOURNALISM WORK ON INTERNET MEDIA Dwi Djauhartono, - Jauhartono, Dwi (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2015)
This study aims to identify and analyze how the concept of the protection of journalistic work, how to setup and protection of works of journalism in online media, and how to dispute settlement piracy and journalistic work through online media. Methods of legal research conducted by normative considerations that the starting point of the analysis in terms of research methods and steps that can be taken to combat piracy of copyright infringement in relation to the work of journalism. The results of this study see the concept of the legal protection of journalistic work, there should be specific legislation governing the work of journalism in online media, because the present arrangement was scattered in several other laws that are less specific set. Settlement of disputes when piracy journalistic work through online media, can be done with two (2) lines, i.e lines in criminal and civil law.